PERAN BAZAR UNIVERSITAS MALAHAYATI DALAM MENINGKATKAN KEWIRAUSAHAAN MAHASISWA - Mufahamah, Euis; Indriani, Wiewiek; Manan, Mohammad Athian; Putri, Fadillah Dwi; Purwanto, Edi; Kurniawan, Adi; Yani, Iis; Suryani, Suryani; Sari, Novita Yuliana (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2023)
This study aims to analyze the impact of the adoption of the MSME bazaar by the Malahayati University in supporting local economic growth. The research method used is primary data collection through a survey of MSME owners participating in the university bazaar, as well as secondary data obtained from relevant sources. The results showed that the adoption of the MSME bazaar by the Malahayati university had a positive effect on increasing sales and exposure of MSME products. In a survey involving MSME owners, most of the respondents reported an increase in the number of customers and income after participating in the university bazaar. In addition, this study also revealed that the presence of the MSME bazaar at Malahayati University could provide additional benefits, such as training in entrepreneurship, marketing and business management for MSME owners. This helps strengthen the capacity of local entrepreneurs to face competition and expand their market reach. This research provides recommendations to universities and related parties to continue to support and develop the MSME bazaar program. Measures such as the use of digital technology to promote MSME products and facilitate access to online markets can be scaled up to expand the positive impact of these activities. This study contributes to our understanding of the role of universities in driving local economic growth through initiatives such as the MSME bazaar.